Death from Malaria infection in a military personnel after a peace keeping mission - Ahmad, Rozali; A., Zakaria; Mohd Sidik, Sherina; Muslan, Muhd Amin; Mohd Taha, Mohd Ghazalli; Muhammad Sued, Muhammad Ello; Sarijan, Samiran; Suirman, Samsuddin; Komeng, Yaakop (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2013)
Military personnel who are deployed for peace-keeping missions are exposed to many hazards, including infectious diseases. One of the most common and fatal infectious disease is Malaria. Although well controlled in Malaysia, this deadly disease is still widely endemic in many other countries especially Africa. We would like to report the case of a military personnel who was infected with Malaria during a peace-keeping mission in Sudan and subsequently died after returning home. We hope that by reporting this case in depth, strategic actions can be taken to avoid similar unfortunate events in future.